Effect of High Tunnel Coverings on Antioxidants of Breaker and Light Red Tomatoes at Harvest and during Ripening - Kelly M. Gude; Channa B. Rajashekar; Brianna Cunningham; Qing Kang; Weiqun Wang; Myungjin Lee; Cary L. Rivard; Eleni D. Pliakoni (Agronomy, 2020)
(1) Background: We assessed the impact of high tunnel coverings and harvest maturity (breaker and light red) on antioxidant capacity, ascorbic acid (AsA), lycopene, β–carotene, and phenolic compound (flavonoid and phenolic acid) accumulation in tomatoes (Solanum lycopersicum) at harvest and postharvest. (2) Methods: The two-year study in Olathe, KS, included six different coverings: a standard polyethylene (standard poly), diffuse poly (diffuse), clear poly (clear), UV-A/UV-B blocking poly (block), 55% shade cloth + standard poly (shade), and removal of standard poly two weeks prior to harvest (movable). (3) Results: Antioxidant capacity increased in fruit grown under the clear covering, compared to the shade covering (p < 0.05); similarly, AsA accumulation increased under the standard and clear coverings, relative to the movable and shade coverings (p < 0.001). Postharvest, at the point of consumption (POC), rutin increased in fruit harvested at light red stage versus breaker stage (p < 0.001), and chlorogenic acid increased in light red harvested fruit by 60% under movable, 55% under shade, and 43% under block covering than breaker harvested fruit (p < 0.01). (4) Conclusions: Based on these results, we conclude that both high tunnel covering and postharvest maturation alter antioxidant capacity, AsA, lycopene, and phenolic compound accumulation profiles by the POC.